2019
DOI: 10.1111/spc3.12452
|View full text |Cite
|
Sign up to set email alerts
|

Economic cycles as a source of social influence on individuals

Abstract: The current review summarizes emerging research in psychology and associated disciplines showing that the economic cycles exert social influence on individuals across a range of psychological domains. Most research on social Economic systems are perhaps the most complicated, powerful, and fascinating outcomes of human social psychological forces. They are made possible through a large-scale willingness to believe in an imaginary entity (money),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Finally, in a sample of freelancers who were purportedly hired to evaluate the work on an intern, those who anticipated an economic downturn were less likely to give constructive feedback to the intern when given the opportunity to do so. Other laboratory experiments have likewise found that signals of a recession lead people to distribute less resources to others (Fisman, Jakiela, & Kariv, 2015;Sirola, 2019Sirola, , 2020.…”
Section: Economic Crisis Logicmentioning
confidence: 94%
“…Finally, in a sample of freelancers who were purportedly hired to evaluate the work on an intern, those who anticipated an economic downturn were less likely to give constructive feedback to the intern when given the opportunity to do so. Other laboratory experiments have likewise found that signals of a recession lead people to distribute less resources to others (Fisman, Jakiela, & Kariv, 2015;Sirola, 2019Sirola, , 2020.…”
Section: Economic Crisis Logicmentioning
confidence: 94%
“…Our study on work–life reconciliation in Lebanon contributes to work–life literature in several ways. Drawing upon research on the impact of the state of the economy and the legal environment on individual behaviour (Bianchi, 2016; Sirola, 2019, 2020), we examine how managers and employees in Lebanese organisations respond to this unique context characterised by economic, financial and political instability and weak labour protection. More generally, we show how work and nonwork responsibilities can be reconciled in a satisfying manner in less supportive contexts by identifying those types of support resources that are most effective when formal support at the national and organisational level hardly exists.…”
Section: Introductionmentioning
confidence: 99%